Entre a cruz e o mercado: estratégias mercadológicas dos neopentecostais na conquista de clientes da fé - Oliveira Junior, Jonas Pereira de (2010)
This dissertation has as objective describing the acting of the Universal Church of God's Kingdom (IURD) of Recife as representant of the brazilian neopentecostalism in the postmodern society. It is described how the church stands out through the merchandising strategies contained in their theologic speech, having this as the main element of differentiation from the others religious groups. This work seeks to identify, through what was observed in the religious ceremonies and sermons preached by the ecclesiastic leadership, the main theological practices of how the religious speech relates, in this specific case, with the postmodernity, so much in the daily basis as well as in the marketing strategies used in the religious dispute.